Renewable energy incentives on the road to sustainable development during climate change: A review - Tryndina, Nicole; An, Jaehyung; Varyash, Igor; Litvishko, Oleg; Khomyakova, Lyubov; Barykin, Sergey; Kalinina, Olga (Frontiers in Environmental Science, 2022)
This review is dedicated to the analytical literature concerning the dynamics of different approaches to renewable energy promotion. Examples of major types of green energy incentives, including carbon tax, Feed-in Tariffs, and investments in research and development are covered in the paper, as well as the barriers and limitations to such practices and the contradictions existing in the field of renewable energy. The dynamics of the means of green energy promotion over this period have been addressed. This review analyzes energy considerations and the importance of raising public awareness on the issue. The evidence collected through the literature analysis, has proven that despite of a significant amount of work done in the field in the transition to the renewable energy sources, including the implementation of various incentives, controversial aspects remain that demand attention both from economists and policymakers. Modern best practices in the field of green energy incentives can be based on government initiatives or stem from the private sector. The most widely used policies for renewable energy promotion discussed in the reviewed studies are tax incentives; however, at the same time, numerous countries are providing fossil fuels subsidies to minimize the level of inequality. Finally, the outlook of different practices concerning financing of the transition from traditional energy sources to renewable ones is presented.